Productivity in the Time of COVID-19 : Evidence from East Asia and Pacific - De Nicola, Francesca; Mattoo, Aaditya; Timmis, Jonathan; Tran, Trang Thu (World Bank, Washington, DC, 2021)
Firms in the East Asia and Pacific (EAP) region have been hit hard by the COVID-19 (coronavirus) pandemic, with dramatic and widespread falls in sales and employment. Firm sales in some EAP countries were 38 to 58 percent lower in April or May 2020, compared to the same month in the previous year. Small and medium-sized enterprises (SMEs) have been particularly affected. The pandemic will have a lasting impact on productivity growth as firm indebtedness and increased uncertainty inhibit investment, and firm closures and unemployment lead to a loss of valuable intangible assets. Support for firms is needed but must be based as far as possible on objective criteria, related not only to past performance or current pain but to the potential for firms, including new firms, to thrive in the future. To avoid unduly prolonging assistance, governments should build exit strategies into the design of support measures and commit to phasing support out by linking it to observable macroeconomic indicators of recovery.